Metal Segregation in Bimetallic CoPd Carbide Carbonyl Clusters: Synthesis, Structure, Reactivity and Electrochemistry of [H6−nCo20Pd16C4(CO)48]n− (n=3–6). Issue 12 (2nd October 2013) - Ciabatti, Iacopo; Fabrizi de Biani, Fabrizia; Femoni, Cristina; Iapalucci, Maria Carmela; Longoni, Giuliano; Zacchini, Stefano
Abstract Nanometric CoPd bimetallic [H6−nCo20Pd16C4(CO)48]n− (n=3–6) tetracarbide carbonyl clusters have been prepared by redox condensation of [Co6C(CO)15]2− with [PdCl2(Et2S)2]. The crystal structures of both the dihydride tetra‐anion and monohydride penta‐anion have been determined as their [NEt4]4[H2Co20Pd16C4(CO)48]⋅4 CH3COCH3 and [NMe3(CH2Ph)][NMe4]4[HCo20Pd16C4(CO)48]⋅5 CH3COCH3 salts, respectively. The two species are isostructural and their structures display a perfect segregation of the two metals. They are composed of a cubic close‐packed (ccp) Pd16 core stabilised on its surface by four {Co5C(CO)12} organometallic fragments. Their polyhydride nature has been corroborated by the study of their reactions with acids and bases, and confirmed by electrochemical studies. In addition, the reactions of [H2Co20Pd16C4(CO)48]4− with Na/naphthalene and PPh3/CO allowed the isolation of other lower nuclearity homoleptic and heteroleptic clusters, that is, [H6−nCo16Pd2C3(CO)28]n− (n=5, 6), [Co4Pd2C(CO)11(PPh3)2], [Co2Pd5C(CO)8(PPh3)5], and [Co4Pd4C2(PPh3)4(CO)10Cl]−. [H6−nCo16Pd2C3(CO)28]n− (n=5, 6) represent the first homoleptic metal–carbonyl clusters containing three interstitial carbide atoms.